The implementation of the Covenant of Mayors initiative in European cities: A policy perspective. (March 2022) - Basso, Matteo; Tonin, Stefania
Highlights: the CoM is one of the world's most significant urban-climate and energy-policy tools. the initiative is considered a success, based on the number of signatories. different barriers and difficulties emerge during the implementation phase. a closer collaboration between EU policy-makers and national governments could overcome the barriers. Abstracts: This paper offers a policy-making perspective on the Covenant of Mayors (CoM) initiative, a tool launched in 2008 by the European Commission to help cities of any size or population implement the 2020 EU Climate and Energy package. By adopting the conceptual framework of "implementation research" it provides insights into the CoM planning process, in particular the implementation phase, which has reached a critical period according to ongoing public and scientific debates. A set of in-depth interviews with selected key informants forms the basis for a discussion of the main barriers and difficulties (technical, financial, and political) that cities face as they attempt to implement the initiative. We argue that a closer collaboration between EU policy-makers and national governments could overcome some critical barriers and diversify the goals of the initiative, making it possible to accommodate the varied capacities of national and local contexts. Future improvements to financial and technical assistance could advance the implementation of several actions proposed by various actors.